Paclitaxel loaded and surface coated n-vinyl caprolactam nanoparticles for breast cancer drug delivery / Mustaqim Abd Rashid - Abd Rashid, Mustaqim (2013)
In this work, a nanoformulation of pacliatxel with biodegradable thermo-responsive N vinyl caprolactam (NYC) is developed for delivery to cancer cells. The thermo responsive graft co-polymeric nanoparticles (PNVC-MAAc) were prepared by dispersion polymerization method, which showed a lower critical solution temperature (LCST). The paclitaxel drug was incorporated into the carrier using cross-linking reaction. After several characterizations, it was found that the nanoformulation developed met the characteristics fit for cancer drug delivery such as appeared in nanometer in size, better morphology and improve the surface charge of the NPs. These results indicated that PTX-PNVC-MAAc NPs could be a promising candidate for cancer drug delivery.